Acute hypertriglyceridemia and hyperglycemia related to mirtazapine: A case report - (:unkn) unknown (KUWAIT MEDICAL ASSOC, 2021)
A 42-year-old woman was hospitalized with depression and was started on mirtazapine 15 mg/day. Just one week after starting mirtazapine, severe hypertriglyceridemia and hyperglycemia were detected. Although these metabolic adverse effects have been reported before, to our knowledge this is the first case of hypertriglyceridemia and hyperglycemia occurring so early (just one week) after initiation of mirtazapine. The patient's glucose and triglyceride normalized nine days after discontinuation of mirtazapine. This case emphasizes the importance of regular glucose and triglyceride measurements at baseline and then regular monitoring in patients receiving mirtazapine treatment.
Keywords: adverse effects; depression; hyperglycemia; hypertriglyceridemia; mirtazapine; INDUCED PANCREATITIS; SECONDARY; INPATIENTS; THERAPY; SAFETY